Shifting timing of intensive nitrogen topdressing later to the stem-elongation phase reduced lower internodes length and lodging risk of wheat - Keisuke Mizuta; Hideki Araki; Tadashi Takahashi (Plant Production Science, 2020)
Intensive nitrogen (N) application during stem elongation is effective in increasing potential yield but it also increases the risk of lodging. Unfortunately, the increased lodging more than offsets any associated gains from the increase in potential yield. We test the hypothesis that lodging is not induced directly by N application during stem elongation but by increased light competition in the resulting excessively dense canopy. Our results show that lodging was more severe in plants given N early (before stem elongation) compared with in plants where N fertilisation was given later (during stem elongation). When N was given early, the lengths of the lower internodes of the tillers were significantly greater than when N was given later. For the early N application, dry weight of the above-ground plant was 75% greater, leaf area index 66% greater and green area index 81% greater than for the later N application. This likely indicates much greater competition for light in the denser canopy with the early N application. Shading treatments applied during stem elongation resulted in the lower internodes being longer and lighter, than for unshaded plants. The results suggest that by shifting intensive N application before stem elongation to during stem elongation, canopy development and thus light competition are reduced, the basal internodes of the tillers are shorter and lodging is minimised.